Health-care providers’ experiences with opt-out HIV testing: a systematic review - Leidel, S.; Wilson, Sally; McConigley, Ruth; Boldy, Duncan; Girdler, Sonya (Routledge, 2015)
HIV is now a manageable chronic disease with a good prognosis, but early detection and referral for treatment are vital. In opt-out HIV testing, patients are informed that they will be tested unless they decline. This qualitative systematic review explored the experiences, attitudes, barriers, and facilitators of opt-out HIV testing from a health-care provider (HCP) perspective. Four articles were included in the synthesis and reported on findings from approximately 70 participants, representing diverse geographical regions and a range of human development status and HIV prevalence. Two synthesized findings emerged: HCP attitudes and systems. The first synthesized finding encompassed HCP decision-making attitudes about who and when to test for HIV. It also included the assumptions the HCPs made about patient consequences. The second synthesized finding related to systems. System-related barriers to opt-out HIV testing included lack of time, resources, and adequate training. System-related facilitators included integration into standard practice, support of the medical setting, and electronic reminders. A common attitude among HCPs was the outdated notion that HIV is a terrible disease that equates to certain death. Some HCPs stated that offering the HIV test implied that the patient had engaged in immoral behaviour, which could lead to stigma or disengagement with health services. This paternalism diminished patient autonomy, because patients who were excluded from opt-out HIV testing could have benefited from it. One study highlighted the positive aspects of opt-out HIV testing, in which participants underscored the professional satisfaction that arose from making an HIV diagnosis, particularly when marginalized patients could be connected to treatment and social services. Recommendations for opt-out HIV testing should be disseminated to HCPs in a broad range of settings. Implementation of system-related factors such as electronic reminders and care coordination procedures should be considered, and a social-justice commitment among HCPs should be encouraged.